ALLEGORIES OF CONQUEST: MISOGYNY AND ANIMAL SYMBOLISM IN COLONIAL BRAZILIAN CHRONICLES - Fonseca, Pedro (2009)
This essay examines through the perspective of cultural criticism the representation of female image in European patriarchal discourse from tradition down to colonial Brazilian chronicles. It shows that denigration of woman is ideological and rhetorical: it corresponds to a cultural complex aiming androcentric hegemony.